Effectiveness of cognitive remediation in depression: a meta-analysis. Issue 16 (14th December 2022) - Legemaat, Amanda M.; Semkovska, Maria; Brouwer, Marlies; Geurtsen, Gert J.; Burger, Huibert; Denys, Damiaan; Bockting, Claudi L.
Abstract: Background: Preliminary evidence suggests beneficial effects of cognitive remediation in depression. An update of the current evidence is needed. The aim was to systematically assess the effectiveness of cognitive remediation in depression on three outcomes. Methods: The meta-analysis was pre-registered on PROSPERO (CRD42019124316). PubMed, PsycINFO, Embase and Cochrane Library were searched on 2 February 2019 and 8 November 2020 for peer-reviewed published articles. We included randomized and non-randomized clinical trials comparing cognitive remediation to control conditions in adults with primary depression. Random-effects models were used to calculate Hedges' g, and moderators were assessed using mixed-effects subgroup analyses and meta-regression. Main outcome categories were post-treatment depressive symptomatology (DS), cognitive functioning (CF) and daily functioning (DF). Results: We identified 5221 records and included 21 studies reporting on 24 comparisons, with 438 depressed patients receiving cognitive remediation and 540 patients in a control condition. We found a small effect on DS ( g = 0.28, 95% CI 0.09–0.46, I 2 40%), a medium effect on CF ( g = 0.60, 95% CI 0.37–0.83, I 2 44%) and a small effect on DF ( g = 0.22, 95% CI 0.06–0.39, I 2 3%). There were no significant effects at follow-up. Confounding bias analyses indicated possible overestimation of the DS and DF effects in the original studies. Conclusions: Cognitive remediation in depression improves CF in the short term. The effects on DS and DF may have been overestimated. Baseline depressive symptom severity should be considered when administering cognitive remediation.